2023
DOI: 10.1039/d2cs00993e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the design of afterglow materials: mechanisms, structural regulation strategies and applications

Xin Yang,
Geoffrey I. N. Waterhouse,
Siyu Lu
et al.

Abstract: Afterglow materials have attracted widespread attention owing to their distinctive and long-lived optical emission properties which create exciting opportunities in various fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 536 publications
(647 reference statements)
0
9
0
Order By: Relevance
“…Dynamic control of UORTP property is a charming target. , Host–guest doping strategy has been offering a great opportunity for the development of stimulus-responsive smart UORTP materials. Theoretically, to achieve dynamic control of UORTP, four pathways are proposed on the basis of host–guest systems: (1) external stimulus can be directly exerted on the host solely; (2) external stimulus can be directly exerted on the guest solely; (3) external stimulus can be exerted on both the host and the guest; (4) external stimulus can be used to alter intermolecular interactions between the host and the guest. Pathways (1) and (4) have been successfully realized in tuning UORTP properties.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic control of UORTP property is a charming target. , Host–guest doping strategy has been offering a great opportunity for the development of stimulus-responsive smart UORTP materials. Theoretically, to achieve dynamic control of UORTP, four pathways are proposed on the basis of host–guest systems: (1) external stimulus can be directly exerted on the host solely; (2) external stimulus can be directly exerted on the guest solely; (3) external stimulus can be exerted on both the host and the guest; (4) external stimulus can be used to alter intermolecular interactions between the host and the guest. Pathways (1) and (4) have been successfully realized in tuning UORTP properties.…”
Section: Introductionmentioning
confidence: 99%
“…RTP refers to the transition of electrons from the lowest excited singlet state (S 1 ) to the lowest excited triplet state (T 1 ) through intersystem crossing (ISC) and then the radiative transition from T 1 to the ground state (S 0 ). If the energy gap between T 1 and S 1 is small enough, the DF is formed when electrons transfer back to S 1 from T 1 by reverse intersystem crossing (RISC) and then return to S 0 radiatively. Recently, Liu et al achieved CD-based circularly polarized RTP (CPRTP) by co-assembling CDs, cellulose nanocrystals (CNCs), and poly­(vinyl alcohol) (PVA). The CPL wavelength can be tuned from 460 to 550 nm by adjusting the content of PVA .…”
mentioning
confidence: 99%
“…Afterglow, known as persistent luminescence, is a fascinating phenomenon in which the materials emit for relatively long periods of time, typically with lifetimes of >0.1 s. In recent years, more attention has been paid to afterglow materials for their promising applications in newly emerged technologies, such as emergency lighting, anticounterfeiting, sensing, etc. To date, most known afterglow systems employ inorganic materials, which generally require ultra-high-temperature forging. , Moreover, the poor compatibility and applicability of the inorganic structures promoted research in organic systems exhibiting afterglow or room-temperature phosphorescence (RTP) properties. A mixture of two or more components is a typical way to obtain the afterglow materials as it could avoid the use of rare earth elements and simplify tedious fabrication processes .…”
mentioning
confidence: 99%
“…To conclude, we designed and synthesized three Czmodified NMI derivatives, NMI-Cz, NMI-2Cz, and NMI-3Cz, and found that the compounds possess significant intramolecular TBCT and TSCT properties. Interestingly, the TBCT process produced fluorescence emission, but the TSCT produced CS first and then formed 3 HLCT via intersystem crossing. When the NMI derivatives are doped into a PMMA film, color-tunable RTP can be observed by inducing ammonia (Scheme 2).…”
mentioning
confidence: 99%